1987
DOI: 10.1016/0165-2427(87)90085-7
|View full text |Cite
|
Sign up to set email alerts
|

Bovine monoclonal antibodies to the F5 (K99) pilus antigen of E. coli, produced by murine/bovine hybridomas

Abstract: Lymph node cells from calves immunized with purified pilus antigen of K99+ enterotoxigenic E. coli (ETEC) were fused with mouse myeloma (NSO) cells, and with non-Ig producing mouse/calf hybridomas or with a bovine Ig-producing mouse/calf/calf secondary hybridoma. Lines secreting bovine monoclonal IgG1 specific for K99 pilus antigen in an ELISA were obtained in each case. The two lines derived from xenohybridoma fusion partners have been secreting anti-K99 bovine monoclonal antibody for over one year in continu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 22 publications
1
20
0
Order By: Relevance
“…Two (73,91) could find no evidence that heteromyelom as offered any advantages. Two other studies (70,78) found that secondary fusion partners gave the best results. Raman et al (90) also reported improvements with rabbit heteromyeloma fusion partners.…”
Section: Heteromyelomas-rationale and Experiencesmentioning
confidence: 94%
See 1 more Smart Citation
“…Two (73,91) could find no evidence that heteromyelom as offered any advantages. Two other studies (70,78) found that secondary fusion partners gave the best results. Raman et al (90) also reported improvements with rabbit heteromyeloma fusion partners.…”
Section: Heteromyelomas-rationale and Experiencesmentioning
confidence: 94%
“…Other viral antigens used include foot and mouth disease, (50 ,80) bovine leukemia, (70,71,81,82 ) bovine viral diarrhea, (77) bovine herpes virus, (83,84) bovine enteric coronavirus, (85) equine infectious anemia, (56,86) equine influenza, (57) and hepatitis A. (87) Work with bacteria and bacterial antigens has generally been confined to infectious diseases of cattle and pigs, including E. coli, (53,78,88) Brucella abortus, (47) and Streptococcus agalacticae, the causitive agent of mastitis, (89 ) Streptococcus pyogenes has also been used as a model antigen in rabbits. (74,90) Antibodies to cellular and tissue antigens have been generated to preparations varying in purity from tissue hom ogenates (37) ; through whole blood (33,49,91) and purified cell populations (28,4 8,90,92) ; to isolated, (23,28,54 ) or recombinant, (41) cellular antigens.…”
Section: Antigens and Immunizationmentioning
confidence: 99%
“…Groves et al reported successful production of stable sheep-mouse hybridomas that secreted sheep MAb against testosterone. Production of a bovine MAb with potential for immunotherapeutic use was achieved by Anderson et al (1987), who re-fused bovine-murine hybridomas to obtain stable lines that secreted bovine MAbs against F5 K99 fimbriae (pili) of ETEC. Comparison of the efficacy of these bovine MAbs with the K99-specific murine MAb described by Sherman et al (1983), for passive protection of calves against ETEC challenge, would be a valuable experiment.…”
Section: Discussionmentioning
confidence: 99%
“…Srikumaran and co-workers have produced monoclonal bovine immunoglobulins of different classes, from fusions of SP2/0 murine myeloma cells with either normal bovine lymphocytes or with lymphocytes from animals immunized against DNP conjugates (Guidry et al, 1986) and used as sources of uniform preparations of bovine immunoglobulin classes. Tucker and her colleagues have developed a number of bovine monoclonal antibodies against blood group determinants (Tucker et al, 1984Anderson et al, 1986) and bacterial antigens (Anderson et al, 1987) using heteromyelomas as well as NSO mouse myeloma cells as the immortal fusion partners. Davidson et al (1982) reported the production of a bovine IgM of undefined specificity by fusing bovine leukemic lymphocytes with NS1 or X63 mouse myeloma cells.…”
Section: Discussionmentioning
confidence: 99%